2011
DOI: 10.1007/s00438-011-0625-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the RING finger gene family in apple

Abstract: The RING finger protein family plays a crucial role in plant growth and development and in response to biotic and abiotic stresses. However, no detailed information concerning this family is available for apple (Malus × domestica L. Borkh) due to the limited information on whole genome sequences. In this study, 688 RING domains in 663 predicted proteins were identified in apple. Based on the spacing between metal ligands or substitutions at one or more of the metal ligand positions, nine RING types were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…Our investigation of gene duplication indicated that the G. hirsutum RH2FE3 gene family expanded through tandem as well as segmental duplication events. The RH2FE3 genes had the same duplication patterns in Arabidopsis (Serrano et al 2006), rice (Lim et al 2010), apple (Li et al 2011), and poplar (Liu et al 2015). Thus, we consider the complexity of RH2FE3 genes is the result of diverse duplication events.…”
Section: Rh2fe3 Genes Of Arabidopsis Rice and Cottonmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation of gene duplication indicated that the G. hirsutum RH2FE3 gene family expanded through tandem as well as segmental duplication events. The RH2FE3 genes had the same duplication patterns in Arabidopsis (Serrano et al 2006), rice (Lim et al 2010), apple (Li et al 2011), and poplar (Liu et al 2015). Thus, we consider the complexity of RH2FE3 genes is the result of diverse duplication events.…”
Section: Rh2fe3 Genes Of Arabidopsis Rice and Cottonmentioning
confidence: 99%
“…RING proteins are responsive to various biological processes (Lyzenga and Stone 2012), including plant growth and development (Li et al 2011;Schwechheimer et al 2009;Zhang et al 2008), hormone signaling pathways (Bu et al 2009), cell cycle, embryogenesis, and biotic and abiotic stress responses (Lee and Kim 2011;Santner and Estelle 2010;Vierstra 2009). The diversified regulatory functions of RING proteins means they are involved in nearly every aspect of plant life, which makes them distinct from other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…For the first method, all of the identified sequences of bZIP proteins from Arabidopsis and rice were used as queries to search the Golden Delicious peptide database (GDR http://www.rosaceae.org/) using software BLASTp [21]. Trying not to miss potential proteins and taking account of credible results, the E value cutoff was set to 0.001 as in references of similar investigations [22]. From this method, about 700 proteins were screened out.…”
Section: Identification Chromosomal Location and Expansion Patterns mentioning
confidence: 99%
“…Presumably these nine genes could be localized to unassembled genomic sequence scaffolds [22]. The number of M.bZIP genes on different chromosomes was variable.…”
Section: Identification Chromosomal Location and Expansion Patterns mentioning
confidence: 99%
See 1 more Smart Citation